Aligned nanofibers of decellularized muscle extracellular matrix for volumetric muscle loss. Issue 6 (13th February 2020) - Patel, Krishna H.; Talovic, Muhamed; Dunn, Andrew J.; Patel, Anjali; Vendrell, Sara; Schwartz, Mark; Garg, Koyal
Abstract: Volumetric muscle loss (VML) is a traumatic loss of muscle tissue that results in chronic functional impairment. When injured, skeletal muscle is capable of small‐scale repair; however, regenerative capacities are lost with VML due to a critical loss stem cells and extracellular matrix (ECM). Consequences of VML include either long‐term disability or delayed amputations of the affected limb. While the prevalence of VML is substantial, currently a successful clinical therapy has not been identified. In a previous study, an electrospun composed of polycaprolactone (PCL) and decellularized‐ECM (D‐ECM) supported satellite cell‐mediated myogenic activity in vitro. In this study, we investigate the extent to which this electrospun scaffold can support functional muscle regeneration in a murine model of VML. Experimental groups included no treatment, pure PCL treated, and PCL:D‐ECM (50:50 blend) treated VML defects. The PCL:D‐ECM scaffold treated VML muscles supported increased activity of anti‐inflammatory M2 macrophages (arginase + ) at Day 28, compared to other experimental groups. Increased myofiber (MHC + ) regeneration was observed histologically at both Days 7 and 28 post‐trauma in blend scaffold treated group compared to PCL treated and untreated groups. However, improvements in muscle weights and force production were not observed. Future studies would evaluate muscle function at longer time‐points post‐VML injury to allow sufficient time for reinnervation of regenerated muscle fibers.